Survey of New, Small-Molecule Isatin-Based Oxindole Hybrids as Multi-Targeted Drugs for the Treatment of Alzheimer’s Disease - Marques, Carolina S.; López, Óscar; Leitzbach, Luisa; Fernández-Bolaños, José G.; Stark, Holger; Burke, Anthony J. (Synthesis, 2022)
In the last decade, our group has been very active at developing and assaying complex libraries of scaffolds with a focus on their potential to identify bioactive drug candidates for neurodegenerative diseases, particularly Alzheimer’s disease (AD). Attention has been focused on isatin-based oxindole scaffolds, for which promising results concerning butyrylcholinesterase (BuChE) inhibitory activity have previously been obtained. Considering some published reports and detailed analysis of the pharmacophores of commercially available drugs for AD (powerful cholinesterase (ChE) inhibitors), we performed a strategic structural modification of the isatin core and generated a new family of isatin-based oxindole hybrids (27 new compounds) possessing crucial key functional units in their framework. The syntheses were accomplished using multiple approaches, including simple N-alkylation reactions, copper-catalyzed amination reactions, and click chemistry. The resulting library was evaluated on ChE and MAO enzymes, both of which are involved in the pathophysiology of neurodegeneration. IC50 values of 1.6 and 2.6 μM (BuChE assays), were achieved for the best inhibitors.
Keywords: isatin-oxindole; hybrids; Alzheimer’s disease (AD); inhibition; cholinesterase (ChE); monoamine oxidase (MAO)